2014
DOI: 10.1177/0309133314544918
|View full text |Cite
|
Sign up to set email alerts
|

Inaccessible Andean sites reveal human-induced weathering in grazed soils

Abstract: Human activity affects properties and development of ecosystems across the globe, to such a degree that it is now challenging to get baseline values for undisturbed ecosystems. This is especially true for soil development, which is potentially affected by land-use history and holds a legacy of past human interventions. Therefore, it is still largely unknown for most ecozones how soil would have developed ‘naturally’. Here, we show undisturbed soil development, i.e. the processes of weathering and accumulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 98 publications
2
22
0
Order By: Relevance
“…5a) usually reduce the effect of Al through complexation: While organic matter in soils can bind to many different substances, it is especially reactive towards the complexation of cations in general and, in particular, to multi-charged cations like Al 3+ and Fe 3+  43 . As all the soils studied had a high organic matter content, and thus a strong binding to Al remaining in the organic matter matrix of the soil, Al 3+ is therefore relatively accumulated in grassland because the less charged cations are more easily leached 26 . This organic matter matrix also buffers the pH lowering effect of Al and explains why there were no significant differences in pH between the different soil types.…”
Section: Discussionmentioning
confidence: 99%
“…5a) usually reduce the effect of Al through complexation: While organic matter in soils can bind to many different substances, it is especially reactive towards the complexation of cations in general and, in particular, to multi-charged cations like Al 3+ and Fe 3+  43 . As all the soils studied had a high organic matter content, and thus a strong binding to Al remaining in the organic matter matrix of the soil, Al 3+ is therefore relatively accumulated in grassland because the less charged cations are more easily leached 26 . This organic matter matrix also buffers the pH lowering effect of Al and explains why there were no significant differences in pH between the different soil types.…”
Section: Discussionmentioning
confidence: 99%
“…This species was found during a large scale ecological study attempting to reconstruct the potential natural vegetation (PNV) and soils of the high-elevation Puna grasslands (see Heitkamp et al 2014 and Sylvester et al 2014 for pilot studies). In this research, pristine zonal vegetation, only accessible with mountaineering equipment, was compared with surrounding slopes which have been grazed and burnt consistently over millennia (Thompson et al 1988; Chepstow-Lusty et al 1996, 2009; Kuentz et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Given that the puna ecosystem's vegetation dynamics have been modified for thousands of years, existence of an undisturbed reference of this vegetation is controversial or according to some studies only found in inaccessible places (Villota and Behling , White , Heitkamp et al. , Sylvester et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, because grazing intensities are variable even within the same area, the resulting vegetation patterns are heterogeneous and respond to site-specific environmental factors (Stohlgren et al 1999). Given that the puna ecosystem's vegetation dynamics have been modified for thousands of years, existence of an undisturbed reference of this vegetation is controversial or according to some studies only found in inaccessible places (Villota and Behling 2013, White 2013, Heitkamp et al 2014.…”
Section: Introductionmentioning
confidence: 99%